Satisfaction as an Experience Engine in Promotion-Intensive Marketplaces: The Roles of Platform-Mediated Relationship Infrastructure and Price Fairness in Repurchase Intention (Shopee, Indonesia) - Rafnelly Rafki; Sarjon Defit; Elfiswandi Elfiswandi (Dinasti Publisher, 2026)
This study investigates how price fairness and platform-mediated relationship infrastructure shape repurchase intention in a promotion-intensive online marketplace, and whether customer satisfaction is the dominant mechanism linking these drivers to repeat buying. Using a cross-sectional survey of active Shopee customers in Indonesia (N = 200), we analysed the model with partial least squares structural equation modelling (PLS-SEM) and tested indirect effects via bootstrapping. Customer satisfaction strongly predicts repurchase intention. Relationship infrastructure captured through responsiveness, assurance, and service recovery significantly increases satisfaction but shows no direct effect on repurchase intention, indicating full mediation through satisfaction. Price fairness does not significantly influence satisfaction and has only a weak direct association with repurchase intention, suggesting that fairness functions more as an acceptability and credibility cue than as a driver of satisfaction. The findings position governable relationship infrastructure as a retention engine and pricing transparency as a procedural safeguard.